Кроссинговер у мейотических мутантов томата - Лисовская, Татьяна Павловна; Кузьмишина, Ирина Ивановна; Коцун, Лариса Александровна; Lisovska, Tetiana P.; Kuzmishyna, Iryna I.; Kotsun, Larysa O. (Institute of Genetics, Physiology and Plant Protection of the ASM, 2015)
Synaptic mutants of tomato as1, dsm1, dsm2 revealed a reduction in the frequency of chiasmata in meiotic cell and normal level of recombination frequency. Mutant sti, which is characterized by impaired chromatin condensation, showed a significant increase in the frequency of crossing-over in homo-and heterozygous state. The phenomenon of incomplete recessive mutant allele (or overdominance normal) allows the use of heterozygous plants in breeding with a view to expanding the range of combinative variability.
Keywords: мейотические мутанты; частота хиазм; кроссинговер; томат; meiotic mutants; chiasma frequency; crossing over; tomato